Cross-Sectional Study: Family Social Support and Self-Harm Behavior in Early Adolescents in the Agricultural Region of Jember Regency - Hamzah, Rizqi Bachtiar; Fitria, Yeni; Kurniyawan, Enggal Hadi; Dewi, Erti Ikhtiarini; Deviantony, Fitrio (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Problems experienced by early adolescents are often triggered by stressors related to physical, cognitive, and emotional changes, which may lead to low self-confidence and self-harming behaviors. These issues can cause psychological distress, thereby increasing the importance of family support. This study aimed to analyze the relationship between family social support and self-harm behavior among early adolescents in the agricultural region of Jember Regency. A correlational research design with a cross-sectional approach was employed. The study population consisted of early adolescents enrolled in public junior high schools (SMPN) in Jember, totaling 2,191 students. A sample of 376 students was selected using proportionate stratified random sampling. Data were collected using the Perceived Social Support from Family (PSS-Fa) questionnaire and the Deliberate Self-Harm Inventory (DSHI). Bivariate statistical analysis using Kendall’s tau-C revealed a significant relationship between family social support and self-harm behavior in early adolescents in the agricultural region of Jember (p = 0.002, r = -0.081). These findings indicate that family social support plays a crucial role in maintaining adolescents' emotional stability and preventing self-harm behaviors resulting from difficulties in adapting to stressors.